Leaving professional competition on the field: Professional collaboration in promoting college athlete mental health - Moore, Matt; Gorczynski, Paul; Aron, Cindy; Bennett, Payton (Frontiers in Psychiatry, 2022)
The wide range of challenges facing college athletes often results in the need for micro and macro mental health services. This article examines a competency-based model of integrated care. A team of mental health professionals must be intentionally created to support athletes throughout various aspects of their unique experience. Interprofessional practice benefits college athletes by providing them with a broad spectrum of care throughout their college experience.